Software for Energy Audit of Households - Pavel Ratner (European Regional Science Association (ERSA), 2014)
Nowadays Russian government pays a lot of attention to solutions of the high energy intensive production system in the country. The key factors of low efficiency of regional energy saving programs is the lack of approved standards and algorithms in the area of energy audit. In practice, both technical and economical parameters of energy audit fluctuate in a very large range. It's due not only to different complexity of the audit but also the immaturity of the market. General population in Russia on its own has not yet embraced energy efficiency as a social value, therefore not many people are interested to invest in increasing energy efficiency of their homes and, therefore, to use algorithms for home energy audit suggested by well-known western companies such as Energy Star and others. New energy efficient home appliances can significantly reduce the energy consumption, however, the extent to which the theoretical reduction potential can be realized highly depends on individual decision processes. In this situation most of the small and middle-size companies as well as government organizations are getting more and more interested in some 'do-it-yourself' tools that can help to make very first steps in introduction of energy management systems and reduce the cost of professional energy audit. In this paper we present a simple interactive calculator, which can be used in individual flats and houses, office buildings and educational institutes such as colleges and schools, for assessment of electricity use by different categories of equipment. The user indicates only type of equipment and its approximate time of work. The program outputs the structure of energy consumption in graphic format. The results of test procedures and the ways for improvement of the program are discussed. The program is realised using the C++ programming language following the C++03 standard. It uses Qt libraries and provides graphical output in the form of a histogram, showing which energy appliances consume the most energy.
Keywords: Q41; Q48; C88; 330; energy efficiency; energy audit; interactive calculator; energy consumption structure